Missing Interactions: The Current State of Multispecies Connectivity Analysis - Wood, Sylvia L. R.; Martins, Kyle T.; Dumais-Lalonde, Véronique; Tanguy, Olivier; Maure, Fanny; St-Denis, Annick; Rayfield, Bronwyn; Martin, Amanda E.; Gonzalez, Andrew (Frontiers in Ecology and Evolution, 2022)
Designing effective habitat and protected area networks, which sustain species-rich communities is a critical conservation challenge. Recent decades have witnessed the emergence of new computational methods for analyzing and prioritizing the connectivity needs of multiple species. We argue that the goal of multispecies connectivity prioritizations be the long-term persistence of a set of species in a landscape and suggest the index of metapopulation capacity as one metric by which to assess and compare the effectiveness of proposed network designs. Here we present a review of the literature based on 77 papers published between 2010 and 2020, in which we assess the current state and recent advances in multispecies connectivity analysis in terrestrial ecosystems. We summarize the four most employed analytical methods, compare their data requirements, and provide an overview of studies comparing results from multiple methods. We explicitly look at approaches for integrating multiple species considerations into reserve design and identify novel approaches being developed to overcome computational and theoretical challenges posed by multispecies connectivity analyses. We conclude that, while advances have been made over the past decade, the field remains nascent in its ability to integrate multiple species interactions into analytical approaches to connectivity. Furthermore, the field is hampered in its ability to provide robust connectivity assessments for lack of a clear definition and goal for multispecies connectivity, as well as a lack of common metrics for their comparison.